The Possibilities of Using the Reds System in Clinical Practice - D. A. Elfimov; I. V. Elfimova; D. D. Harchenko; A. E. Chuprakov; N. V. Tjumenceva (Архивъ внутренней медицины)
A review of the literature is presented, which describes a unique mobile non-invasive system for measuring the total volume of fluid in the lungs ReDS, a study of its effectiveness on animals and volunteers, as well as experience of use in clinical practice. An analysis of domestic and foreign literary sources of the portals PubMed, Web of Science, Nature, published in the period from 2012–2024, was carried out. Every year around the world there is a tendency to increase the number of patients with chronic heart failure. The key problem of the diagnostic search remains the early detection of decompensation of chronic heart failure. One of the reliable and early markers of impending acute decompensation of chronic heart failure is monitoring of the fluid volume in the lungs. Determining the fluid volume indicator can serve as a criterion for adjusting the therapy, which, in turn, should affect the frequency of re-hospitalizations. Thus, vital for the further management of patients with acute decompensation of chronic heart failure is the control of volume, as well as the identification and quantification of the degree of congestion. Fluid volume assessment is a key factor in the management of patients with chronic heart failure in inpatient and outpatient settings. ReDS monitoring significantly reduces the likelihood of readmission to hospital with chronic heart failure within 3 months compared with patients not tested on the ReDS system.